2015
DOI: 10.1074/mcp.m115.051383
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Phosphoproteome Dynamics Induced by an ATP Synthase Inhibitor Citreoviridin*

Abstract: Citreoviridin, one of toxic mycotoxins derived from fungal species, can suppress lung cancer cell growth by inhibiting the activity of ectopic ATP synthase, but has limited effect on normal cells. However, the mechanism of citreoviridin triggering dynamic molecular responses in cancer cells remains unclear. Here, we performed temporal phosphoproteomics to elucidate the dynamic changes after citreoviridin treatment in cells and xenograft model. We identified a total of 829 phosphoproteins and demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 74 publications
(88 reference statements)
0
19
0
Order By: Relevance
“…This category contains the two HSP90 isoforms (HSP90AA1 and HSP90AB1), which harbor PTM sites involved in the regulation of the chaperone activity (Mollapour and Neckers, 2012). These isoforms are known to be phosphorylated at Ser263 and Ser255, respectively (Hu et al, 2015; Wang et al, 2017), within the CK2 phosphorylation motif (S-X-X-E) that is crucial for protein activity. In particular, phosphorylation at Ser255 is required for the activation of MAPK/ERK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This category contains the two HSP90 isoforms (HSP90AA1 and HSP90AB1), which harbor PTM sites involved in the regulation of the chaperone activity (Mollapour and Neckers, 2012). These isoforms are known to be phosphorylated at Ser263 and Ser255, respectively (Hu et al, 2015; Wang et al, 2017), within the CK2 phosphorylation motif (S-X-X-E) that is crucial for protein activity. In particular, phosphorylation at Ser255 is required for the activation of MAPK/ERK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…8,13 Additionally, using homology modeling and docking simulation, aurovertin B and citreoviridin were screened out to inhibit ATP synthase and found to trigger cancer cell death. We proved that citreoviridininduced response network was involved in protein folding by proteomics and phosphoproteomics 5,13 Furthermore, targeting both ectopic ATP synthase and 26s proteasome induces ER stress in breast cancer cells. 20 In vivo study showed that citreoviridin induces alterations in the expression of glucose metabolism-related enzymes in lung cancer.…”
Section: Proteomes For Molecular Regulation Studiesmentioning
confidence: 99%
“…The categories of bioinformatics contain many subfields such as sequence analysis, genome annotation, transcriptome and proteome analyses, as well as network biology and dynamic modeling. 5 Both network biology and modeling are important in the study of systems biology. 1 Network biology includes network and pathway analyses which help researchers understand the relationships within metabolic, protein-protein interaction networks and phospho-signaling pathways.…”
Section: Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of modification sites is 338,948 on 20,368 proteins, where seventy-three percent are phosphorylation, 15% ubiquitination and 8% acetylation 19 . To date, a global analysis of serine-, threonine-, and tyrosine-phosphorylation has been performed using advanced mass-spectrometric techniques combined with hydroxy acid-modified metal oxide chromatography (HAMMOC) 20 , 21 . HAMMOC is a precise and popular phosphopeptide enrichment method that uses metal oxide chromatography modified with aliphatic hydroxyl acids to reduce the non-specific binding of acidic amino acid for large-scale study of phosphorylated proteins 22 24 .…”
Section: Introductionmentioning
confidence: 99%